Monitoring of Global and National Consumer Trends — Importance Stage of Strategizing (Based on Rabbit Industry) - K. I. Shaklein (Управленческое консультирование, 2018)
The aim of the article is to determine the objective trends directly and indirectly influencing the development of the rabbit industry at the global and national levels. This research was carried out in accordance with the methodology of the general theory of strategy developed by Vladimir Kvint. The main methods for analyzing the identified trends are based on statistical and econometric methods. In the process of analysis at the global level, the following trends are noted: the growing deficit in the consumption of dietary products, the conduct of activities by public organizations (UN) to improve the quality of nutrition, the growing interest of the population in a healthy diet, a healthy lifestyle. At the national level, the identified trends have been confirmed. The existing trends define stable prospects in the field of rabbit industry development.